2008
DOI: 10.1007/s00705-008-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological and molecular characterization of a putative new sobemovirus infecting Imperata cylindrica and maize in Africa

Abstract: A new virus was isolated from both the grass Imperata cylindrica and maize plants that had yellow mottle symptoms in Burkina Faso, West Africa. The virus has isometric particles ca. 32 nm in diameter. The experimental host range was restricted to Rottboellia exaltata. Virions were isolated from leaves of systemically infected maize plants. Koch's postulates were completed by mechanically inoculating uninfected Imperata or maize with either purified virus or sap from infected Imperata plants. Virion preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Up to now, 11 sobemovirus genomes have been fully sequenced. All sequenced sobemoviruses exhibit common genomic organization: the RdRp is encoded by ORF2b by the −1 PRF mechanism (McGavin and Macfarlane, 2009;Meier and Truve, 2007;Sérémé et al, 2008). The analysis of their cis-acting −1 PRF signals indicate the presence of an identical UUUAAAC slippery sequence, a seven nucleotide spacer region 1 (exception is Ryegrass mottle virus where the spacer is 8 nucleotides long), and a putative stem-loop secondary structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 11 sobemovirus genomes have been fully sequenced. All sequenced sobemoviruses exhibit common genomic organization: the RdRp is encoded by ORF2b by the −1 PRF mechanism (McGavin and Macfarlane, 2009;Meier and Truve, 2007;Sérémé et al, 2008). The analysis of their cis-acting −1 PRF signals indicate the presence of an identical UUUAAAC slippery sequence, a seven nucleotide spacer region 1 (exception is Ryegrass mottle virus where the spacer is 8 nucleotides long), and a putative stem-loop secondary structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms observed on Imperata cylindrical were more similar to those of rice yellow mottle disease. The non-detection of RYMV in this species suggested that these symptoms may be probably due to Imperata yellow mottle virus, a Sobemovirus closely related to RYMV [19] which were found in West Africa [20].…”
Section: Discussionmentioning
confidence: 86%
“…SMAMV clustered with RYMV and IYMV but the bootstrap support was low due to the short sequences used and high divergence between viruses. However, it is noteworthy that SMAMV clustered with RYMV and IYMV, two sobemoviruses also reported only from Africa (8).…”
Section: Resultsmentioning
confidence: 94%